Drawing the process - Davies, Jo; Duff, Leo (Intellect, 2005)
A major International conference on this theme took place in January 2003. To coincide with this event, this book documents and expands upon the theme of ''drawing the process.'' Much debate and research is currently undertaken in this area and it is the intention of the book to galvanise this, while providing a vehicle for deep enquiry. The publication will firstly comprise a collection of refereed papers representing a breadth of activity and research around the issues of drawing within the broad context of art and design activity. The second dimension of the book will be an examination of t.